Conversational analysis: Between the structure and the sense - Valls, Amparo Tusón (Sociolinguistic Studies, 2002)
In this paper we are presenting some basic approaches that formulate the theoretical and methodological framework of the conversational analysis. On the one hand, we formulate the instruments that allow us to analize the conversations from a systemic point of view, bearing in mind their organization in speak turns. On the other hand, we pay attention to the mechanisms that people use to produce and to interpret the conversational sense in the local context, through the articulation of the linguistic forms and the non linguistic items that constitute the communicative interactions. The paper is concluding with some practical orientations about the gathering and treatment of conversational data.